1991
DOI: 10.1093/ajcn/53.4.1027s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a palm-oil-vitamin E concentrate on the serum and lipoprotein lipids in humans

Abstract: The effect of a capsulated palm-oil-vitamin E concentrate (palmvitee) on human serum and lipoprotein lipids was assessed. Each palmvitee capsule contains approximately 18, approximately 42, and approximately 240 mg of tocopherols, tocotrienols, and palm olein, respectively. All volunteers took one palmvitee capsule per day for 30 consecutive days. Overnight fasting blood was taken from each volunteer before and after the experiment. Serum lipids and lipoproteins were analyzed by using the enzymatic CHOD-PAP me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 12 publications
3
46
0
1
Order By: Relevance
“…Clinical findings concerning the effects of T3 on circulating cholesterol, triglycerides and lipoproteins in humans are inconsistent. The four earlier studies published by Tan et al 16) and Qureshi et al 12,17) showed lipid-lowering effects (total cholesterol, LDL and triglyceride reduction) of the T3-rich fraction (TRF) from palm oil. In these studies, no changes were found in serum HDL cholesterol concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical findings concerning the effects of T3 on circulating cholesterol, triglycerides and lipoproteins in humans are inconsistent. The four earlier studies published by Tan et al 16) and Qureshi et al 12,17) showed lipid-lowering effects (total cholesterol, LDL and triglyceride reduction) of the T3-rich fraction (TRF) from palm oil. In these studies, no changes were found in serum HDL cholesterol concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported that the effects of tocotrienols and tocotrienol-rich fractions on lipid metabolism in animals [26]- [29] and humans [30]- [33]. The mechanism of the hypocholesterolemic effect of tocotrienols was revealed as the suppression of 3-Hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase activity and inhibition of expression of HMGCoA reductase mRNA [21] [34].…”
Section: Discussionmentioning
confidence: 99%
“…42 What added to the interest in tocotrienol as a cholesterol-lowering nutrient in humans was a concurrent independent study reporting the hypocholesterolemic effects of palmvitee. 43 Each palmvitee capsule contained approximately 18, 42, and 240 mg of tocopherols, tocotrienols, and palm olein, respectively. All volunteers took one palmvitee capsule per day for 30 consecutive days.…”
Section: Hypercholesterolemic Effectsmentioning
confidence: 99%
“…The magnitude of reduction of serum total cholesterol ranged from 5.0% to 35.9% whereas the reduction of low-density-lipoprotein cholesterol values ranged from 0.9% to 37.0% when compared with their respective baseline values. 43 Tocotrienol, not only of palm oil origin, but also isolated from rice bran show cholesterol lowering properties. 44,45 Amaranth oil, containing tocotrienol, possesses hypocholesterolemic properties as well.…”
Section: Hypercholesterolemic Effectsmentioning
confidence: 99%
See 1 more Smart Citation